Large‐Scale Particle Image Velocimetry Reveals Pulsing of Incoming Flow at a Stream Confluence. Issue 9 (21st September 2021) - Sabrina, Sadia; Lewis, Quinn; Rhoads, Bruce
Abstract: Despite widespread recognition that confluences are characterized by complex hydrodynamic conditions, few studies have mapped in detail spatial patterns of flow at confluences and variation in these patterns over time. Recent developments in large‐scale particle image velocimetry (LSPIV) have created novel opportunities to explore the spatial and temporal dynamics of flow patterns at confluences. This study uses LSPIV to map two‐dimensional flow structure at the water surface at a confluence and to examine variation in this structure over time. Results show that flow within the confluence is characterized by a large region of flow stagnation at the junction apex, a region of low velocities at the downstream junction corner, and a region of merging of the two flows along a mixing interface within the center of the confluence. Interaction between the incoming flows varies over time in the form of episodic pulsing in which one of the two tributary flows first decelerates and then subsequently accelerates into the confluence. The cause of this pulsing remains uncertain, but it may reflect unsteadiness in the water‐surface pressure‐gradient field as the two flows compete for space within the confluence. No large‐scale vortices are evident within the mixing interface for the particular flow conditions documented in this study, but such vortices do occur along the margins of the stagnation zone where shearing action between fast‐moving and slow‐moving fluid is strong. The results of the study provide insight into the time‐dependent dynamics of the spatial structure of flow at stream confluences. Key Points: Large‐scale particle image velocimetry (LSPIV) reveals spatial and temporal variation in confluence flow structure at high spatial resolution Interaction of incoming flows within a confluence is characterized by episodic pulsing of flow from the main tributary Fluid motion in a region of flow stagnation varies in direction over time and is influenced by large shear‐generated vortices